The Effectiveness of Teaching Materials Loaded with Blended Learning with a Scientific Approach on Buffer Solution Learning - Susilaningsih, Endang; Aprilia, Nurkintan; Hayati, Sri (Universitas Negeri Semarang, 2022)
The 2013 scientific-based curriculum, teachers must facilitate students to gain knowledge or skills based on the scientific method. The research aims to analyze the effectiveness of teaching materials. This type of research development, teaching materials have valid content and media. Teaching materials are declared effective if there is an increase in students' classical mastery, an increase in the achievement of basic competencies, and students can understand macroscopic, microscopic and symbolic level representations. Quantitative descriptive research method, starting from the analysis of the quality of teaching materials and diagnostic test instruments Two Tier Multiple Choice (TTMC), application of teaching materials, application of questions, data analysis of test results, classical completeness, achievement of basic competencies, and analysis of representational understanding. The research subjects were students of class XI and XII MIPA. The results of the study were obtained from the results of the student's TTMC test on the buffer solution material that had used Teaching Materials. Data analysis was done classically. The results showed that there was an increase in classical completeness by 9%, the achievement of basic competence indicators increased by 8% and concept understanding increased by 6%. So that the teaching materials developed are effective to use.